Kampanye Public Relations Bagi Kopi “Bagi Keliling” - Hanum Muti Salshabila; Marsha Amina Safira; Sadiyah El Adawiyah (CV. ITTC INDONESIA, 2026)
In today's coffee industry, competition is increasingly fierce. Many coffee entrepreneurs are not only selling coffee but also providing customer comfort through their coffee shops. However, the main challenge lies in maintaining brand existence amid the many choices available to consumers. Increasing coffee shop brand awareness is considered very important to enhance its existence in the community, especially among the coffee shop's target market. One way to increase coffee shop brand awareness is through public relations campaigns. This is considered quite effective because a campaign will directly involve their target marketing customers through interactions that occur during the campaign. Campaign publicity activities also need to be carried out, as publicity is proof that the campaign is running smoothly. Observing social media shows that a company's publicity activities are tailored to their target audience, which is key to successfully conveying their message. Many coffee shops target young people, such as college students, so many coffee shops promote or publicize their activities through social media, which is often accessed by college students.